A Comparative Study of Intranasal Corticosteroids versus Antihistamines in the Management of Persistent Allergic Rhinitis in Indonesia - Mariana Alifah; Abhimanyu Putra; Zainal Abidin Hasan; Aisyah Andina Rasyid; Sari Sulistyoningsih (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Allergic rhinitis (AR) is a prevalent chronic inflammatory disease in Indonesia. Intranasal corticosteroids (INCS) and antihistamines are commonly prescribed treatments, but their comparative effectiveness in the Indonesian context remains unclear. This study aimed to compare the efficacy and safety of INCS versus antihistamines in managing persistent AR in Indonesia. Methods: A randomized controlled trial was conducted involving 120 patients diagnosed with persistent AR according to the Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines. Participants were randomly assigned to receive either INCS (fluticasone propionate) or oral antihistamines (cetirizine) for eight weeks. The primary outcome was the change in the Total Nasal Symptom Score (TNSS), and secondary outcomes included the Rhinoconjunctivitis Quality of Life Questionnaire (RQLQ) score and adverse events. Results: Both INCS and antihistamines significantly improved TNSS and RQLQ scores from baseline. However, the INCS group demonstrated a significantly greater reduction in TNSS scores compared to the antihistamine group (p<0.05) at weeks 4 and 8. No significant difference was found between the two groups in terms of RQLQ score improvement. Both treatments were well-tolerated, with mild and transient adverse events reported in both groups. Conclusion: INCS are more effective than antihistamines in controlling nasal symptoms in patients with persistent AR in Indonesia. Both treatments improve quality of life, with comparable safety profiles. These findings support the preferential use of INCS as first-line therapy for persistent AR in the Indonesian population.